Le plan local d’urbanisme : un champ d’extension de la protection patrimoniale ? - Mathieu Gigot; Sébastien Jacquot; Julie Marchand; Vincent Veschambre (Territoire en Mouvement)
This article is based on the results of a research project devoted to the notion of “PLU patrimonial”, an expression which refers to the french local development plan (PLU) integrating heritage issues and policies. The research project aims to draw up an inventory of the way in which local authorities have defined the tools of identification and protection of heritage in the framework of the elaboration of their PLU. We have focused here on several municipalities of large French cities, for a comparative analysis of these PLUs, enriched by interviews and field analyses with the actors of their elaboration. This analysis shows that heritage is clearly one of the obligatory stake in a PLU, generally in connection with other issues, and its importance may vary in relation with the political ambition in the matter. Within the framework of the elaboration of these PLUs, various actors participate in the definition of heritage, which can lead to a geographical and typological extension of heritage. Through the integration of heritage in local development plans, there is a tendency towards the immaterialization of this notion, bringing it closer to the notions of living environment and landscape. This research also studied the specific regulatory writing, to reveal the great differences in the degrees of constraints and protection between the various PLUs and to study the ways of articulating the PLU with specific tools of protection and heritage planning. In some cases, the integration of heritage is so developed that we can qualify it as “heritage PLU”. It undoubtedly enriches the set of legal and regulatory instruments concerning heritage identification and preservation.